Twitter Sentiment Analysis on Halal Cosmetics - Siti Maysyaroh; Aam Slamet Rusydiana (SMART Insight, 2023)
This study aims to analyze sentiments related to halal cosmetic products through data taken from the Twitter social media platform. The method used in this research is sentiment analysis using a Python library known as VADER (Valence Aware Dictionary and Sentiment Reasoner). The data retrieved includes tweets with keywords related to